Silicon-carbon composite material, preparation method thereof, pole piece and battery
By using hydrogen bonding and electrostatic adsorption in silicon-carbon composite materials to form a specific hierarchical structure, the problems of high expansion rate and poor circulation performance in batteries are solved, and low expansion rate and excellent circulation stability are achieved, improving the The overall performance of the battery.
Patent Information
- Application Number
- CN202411516622.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-14
AI Technical Summary
The existing silicon-carbon composite materials have a high expansion rate and poor circulation performance in battery applications, making it difficult to achieve uniform carbon coating and avoid agglomeration, which affects the stability and capacity of the battery.
By using hydrogen bonds and electrostatic adsorption in silicon-carbon composite materials, a structure consisting of a silicon-carbon core, a coupling agent layer and a conductive carbon layer are formed. The silicon-carbon core accounts for 90%-99.5% and the coupling agent layer is 0.5%-6. %, the conductive carbon layer is 0.01%-2%. The conductive carbon material is firmly coated on the surface of silicon carbon material by hydrogen bonding and electrostatic action, reducing the shedding and agglomeration of conductive materials.
The low expansion rate of the electrode and excellent cycle stability are achieved, which improves the first charging capacity and cycle performance of the battery, while reducing production costs.
Smart Images

Figure CN119315014A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite material and a preparation method thereof, a pole piece and a battery. Background Art
[0002] Energy crisis and environmental problems are becoming increasingly prominent in today's society. New clean energy and energy storage have become a hot topic of research. Chemical energy storage technology has good development prospects due to its advantages of being free from geographical restrictions, flexible construction, and adjustable capacity. Among them, lithium-ion batteries have broad application prospects in portable consumer electronics, electric vehicles, large-scale energy storage equipment, distributed mobile power supplies, etc. due to their high energy density, high power density, long life, and environmental friendliness. With the requirements of the Ministry of Industry and Information Technology and other ministries for the specific energy of power battery cells to reach "300Wh / Kg", and the rapid increase in demand for battery energy density in other fields, it is particularly urgent to develop lithium-ion batteries with higher energy density. At present, the negative electrode material of lithium batteries is mainly graphite. Although it has the advantages of high conductivity and stability, its development in energy density has approached its theoretical maximum value of 372mAh / g, which cannot meet the market's growing demand for energy density. Finding a new type of high-capacity, safe and long-cycle material to replace graphite negative electrode materials has become the key to the further development of power lithium-ion batteries. The theoretical capacity of silicon is as high as 4200 mAh / g, which has great development potential.
[0003] Silicon has an ultra-high specific capacity and low lithium insertion potential, but in actual battery applications, silicon materials still face urgent problems to be solved. Silicon is a semiconductor material, and its conductivity is much lower than that of graphite. At present, silicon-carbon materials are generally used to improve its conductivity. However, in the prior art, some silicon-carbon materials require strong acid to etch magnetic foreign matter during the preparation process, which may cause internal short circuits and enrichment of dendrites in the battery to pierce the diaphragm, as well as reduce capacity and first efficiency; some silicon-carbon materials are difficult to make the carbon material coat evenly, firmly, and avoid agglomeration, which affects its expansion rate and cycle performance. Summary of the invention
[0004] In order to solve the problem that the silicon-carbon composite material in the prior art has a high expansion rate when applied to electrodes and poor cycle performance when applied to batteries, a silicon-carbon composite material and a preparation method thereof, an electrode sheet, and a battery are provided. The electrode prepared from the silicon-carbon composite material has a low expansion rate, and the prepared battery has excellent cycle stability.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention provides a silicon-carbon composite material, which comprises a silicon-carbon core, a coupling agent layer and a conductive carbon layer in sequence from the inside to the outside, wherein the coupling agent layer is connected to the surface of the silicon-carbon core through hydrogen bonds, and the conductive carbon layer is connected to the surface of the coupling agent layer through electrostatic action.
[0007] In the present invention, preferably, the mass percentage of the silicon-carbon core to the silicon-carbon composite material is 93%-99.5%, for example, 96%, 97.5%, 98.03% or 98.5%.
[0008] In the present invention, preferably, the coupling agent layer accounts for 0.5%-6% by mass of the silicon-carbon composite material, for example, 1%, 1.96%, 2% or 5.6%.
[0009] In the present invention, preferably, the mass percentage of the conductive carbon layer to the silicon-carbon composite material is 0.01%-2%, for example, 0.5%.
[0010] In a specific embodiment of the present invention, the silicon-carbon core accounts for 97.5% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 2% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.5% of the mass percentage of the silicon-carbon composite material.
[0011] In a specific embodiment of the present invention, the silicon-carbon core accounts for 98.5% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 1% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.5% of the mass percentage of the silicon-carbon composite material.
[0012] In a specific embodiment of the present invention, the silicon-carbon core accounts for 93.9% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 5.6% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.5% of the mass percentage of the silicon-carbon composite material.
[0013] In a specific embodiment of the present invention, the silicon-carbon core accounts for 98.03% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 1.96% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.01% of the mass percentage of the silicon-carbon composite material.
[0014] In a specific embodiment of the present invention, the silicon-carbon core accounts for 96% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 2% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 2% of the mass percentage of the silicon-carbon composite material.
[0015] In the present invention, preferably, the silicon carbon core comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon.
[0016] In the present invention, preferably, the surface of the silicon-carbon core contains hydroxyl groups.
[0017] In the present invention, the coupling agent layer includes a coupling agent, and the coupling agent is preferably a silane coupling agent, and more preferably a silane coupling agent containing amino groups and methyl groups, such as 3-aminopropyltrimethoxysilane (APTMS).
[0018] In the present invention, the conductive carbon layer comprises a conductive carbon material, and the conductive carbon material is preferably carbon nanotube (CNT) or graphene, and more preferably carbon nanotube.
[0019] Wherein, the carbon nanotubes are preferably single-walled carbon nanotubes.
[0020] In the present invention, preferably, the coupling agent layer is positively charged, and the conductive carbon layer is negatively charged.
[0021] The present invention also provides a method for preparing a silicon-carbon composite material, which comprises the following steps:
[0022] S1, mixing a silicon-carbon material and a solution containing a coupling agent to obtain a silicon-carbon intermediate material;
[0023] S2, mixing the silicon-carbon intermediate material and the conductive carbon material, and performing a second solvent removal to obtain a silicon-carbon composite material;
[0024] Wherein, the silicon-carbon material and the coupling agent contain functional groups that can generate hydrogen bonds between the two;
[0025] Wherein, the surface of the coupling agent and the surface of the conductive carbon material have opposite charges.
[0026] In the present invention, preferably, the surface of the silicon-carbon material contains hydroxyl groups.
[0027] The mass content of hydroxyl groups in the silicon-carbon material is preferably 0.5%-2%, for example 1%, wherein % means the mass of hydroxyl groups as a percentage of the mass of the silicon-carbon material.
[0028] In the present invention, the mass content of the hydroxyl group of the silicon-carbon material can be determined by the following method:
[0029] Weigh Wg of silicon-carbon material and put it into a 100mL conical flask, add 80mL of 0.05N sodium hydroxide aqueous solution, cover the conical flask, and stir the mixture at room temperature for 24 hours with a magnetic stirrer. Then separate the mixture by centrifugation, and take 10mL of the solution obtained by centrifugation. Before the titration process, add 0.5g of phenolphthalein to a mixture of 50mL of ethanol and 50mL of distilled water. Use three drops of phenolphthalein solution as an indicator and further titrate with a certain volume of 0.05N hydrochloric acid aqueous solution (recorded as A) to neutralize (the color changes from purple to transparent). Repeat the above steps with a blank solution (0.05N sodium hydroxide, without silicon-carbon sample), and record the volume of hydrochloric acid used to neutralize the blank solution as B. Among them, the units of A and B are both mL. X is the amount of hydroxyl group per unit mass of silicon-carbon material, which is calculated as follows: X (mM / g) = (BA) * 0.05 * 8 / W; the mass content of hydroxyl group in silicon-carbon material = X * 17 * 100%.
[0030] In the present invention, preferably, the surface of the coupling agent is positively charged.
[0031] Preferably, the coupling agent contains an amino group, and the coupling agent further contains at least one of a methyl group and a hydroxyl group.
[0032] The mass content of the amino group of the coupling agent is preferably 8%-10%, for example 9%, wherein % means the mass of the amino group accounts for the mass of the coupling agent.
[0033] In the present invention, preferably, the surface of the conductive carbon material carries a negative charge.
[0034] In the present invention, preferably, the field emission threshold electric field strength of the conductive carbon material is 1-3 V / μm, for example, 2 V / μm.
[0035] In the present invention, preferably, the field emission current density of the conductive carbon material is 0.5-3A / cm 2 , for example 1A / cm 2 .
[0036] In the present invention, the coupling agent is preferably a silane coupling agent, more preferably a silane coupling agent containing an amino group and a methyl group, such as 3-aminopropyltrimethoxysilane (APTMS).
[0037] In the present invention, the solvent in the solution containing the coupling agent is, for example, one or more of methanol, ethanol, ethyl acetate, toluene and tetrahydrofuran.
[0038] The mass concentration of the coupling agent in the solution containing the coupling agent is preferably 0.5%-10%, for example 1% or 3%, wherein % means the mass of the coupling agent as a percentage of the mass of the solution containing the coupling agent.
[0039] In the present invention, the conductive carbon material is preferably carbon nanotube (CNT) or graphene, more preferably carbon nanotube.
[0040] Wherein, the carbon nanotubes are preferably single-walled carbon nanotubes.
[0041] In the present invention, the silicon-carbon material comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon, and the mass content of silicon in the silicon-carbon material is preferably 40%-60%, for example, 50%. Wherein, % means the percentage of the mass of silicon to the mass of the silicon-carbon material.
[0042] In the present invention, the silicon-carbon material comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon, and the mass content of the porous carbon in the silicon-carbon material is preferably 37%-57%, wherein % means the percentage of the mass of the porous carbon to the mass of the silicon-carbon material.
[0043] In the present invention, the mass percentage of the coupling agent to the silicon-carbon material is preferably 0.5%-6%, for example 1%.
[0044] In the present invention, the mass percentage of the conductive carbon material to the silicon-carbon material is preferably 0.01%-2%, for example 0.5%.
[0045] In the present invention, since there are suspended hydroxyl groups on the surface of the silicon-carbon material and the coupling agent contains at least one of methyl and hydroxyl groups, hydrogen bonds are generated between the hydroxyl groups on the surface of the silicon-carbon material and the methyl groups in the coupling agent or the hydroxyl groups in the coupling agent through in-situ polymerization, so that they are tightly combined, so that there are suspended amino groups (-NH2) on the surface of the silicon-carbon intermediate material, so that the silicon-carbon intermediate material is positively charged, and the silicon-carbon intermediate material and the conductive carbon material with a negative charge on the surface are firmly adsorbed together due to electrostatic adsorption.
[0046] In the present invention, the preparation of the silicon-carbon material includes, for example, the following steps: The preparation of the silicon-carbon material includes the following steps: mixing porous carbon and a gas silicon source for CVD silicon deposition, and then mixing with a gas carbon source for CVD carbon coating to obtain a silicon-carbon material. In the preparation of the silicon-carbon material of the present invention, the directly deposited nano-silicon has high activity, and simple CVD carbon coating can prevent it from spontaneous combustion due to direct contact with air and water.
[0047] The gaseous silicon source refers to a compound containing silicon element, and the silicon source is preferably silane, and the silane is preferably monosilane.
[0048] Wherein, the gaseous carbon source is preferably alkyne.
[0049] Wherein, the alkyne is preferably acetylene.
[0050] Wherein, the CVD silicon deposition preferably includes a heating stage and a heat preservation stage.
[0051] The temperature in the insulation stage is preferably 100-600°C, for example 550°C.
[0052] The duration of the heat preservation stage is preferably 6-7 hours, for example 6.5 hours.
[0053] Wherein, the CVD silicon deposition is preferably performed in nitrogen.
[0054] The CVD silicon deposition is performed in a fluidized bed, for example.
[0055] Preferably, when the porous carbon is heated to 500° C., a gaseous silicon source is introduced into the fluidized bed.
[0056] The flow rate of the gaseous silicon source into the fluidized bed is preferably 5-20 L / min, for example 10 L / min.
[0057] The flow rate of the gaseous carbon source into the fluidized bed is preferably 5-20 L / min, for example 10 L / min.
[0058] Wherein, the flow rate of the nitrogen is preferably 40 L / min.
[0059] In the present invention, preferably, the second desolventizing method comprises spray drying and / or rotary evaporation.
[0060] Wherein, the spray drying equipment is preferably an open spray drying equipment.
[0061] Wherein, the inlet air temperature of the spray drying is preferably 100-180°C.
[0062] Wherein, the outlet air temperature of the spray drying is preferably 50-90°C.
[0063] Wherein, the feed rate of the spray drying is preferably 10-40 L / min.
[0064] In the present invention, preferably, after mixing the silicon-carbon material and the solution containing the coupling agent, a first solvent removal step is further included.
[0065] The first desolventizing method is, for example, rotary evaporation.
[0066] In the present invention, preferably, in step S2, the silicon-carbon intermediate material is dissolved and then mixed with the conductive carbon material.
[0067] The solvent used for dissolution is, for example, one or more of methanol, ethanol, ethyl acetate, toluene and tetrahydrofuran.
[0068] In certain specific embodiments of the present invention, the method for preparing the silicon-carbon composite material comprises the following steps: S1, mixing the silicon-carbon material and the solution containing the coupling agent, performing the first desolventizing step, and obtaining a silicon-carbon intermediate material; S2, dissolving the silicon-carbon intermediate material and mixing it with the conductive carbon material, performing the second desolventizing step, and obtaining a silicon-carbon composite material. The first desolventizing step, the dissolving step, and the second desolventizing step can further reduce the bonding of the silicon-carbon material and the conductive carbon material through chemical bonds with weak bonding force, thereby further reducing the phenomenon of shedding during the subsequent homogenization process of the battery.
[0069] In some other specific embodiments of the present invention, the method for preparing the silicon-carbon composite material includes the following steps: S1, mixing the silicon-carbon material and a solution containing a coupling agent to obtain a mixed solution containing a silicon-carbon intermediate material; S2, then mixing the mixed solution with a conductive carbon material, performing a second desolventizing step, and obtaining a silicon-carbon composite material.
[0070] In certain specific embodiments of the present invention, the second solvent removal further includes a heat treatment step.
[0071] The temperature of the heat treatment is preferably 400-800°C, for example 600°C.
[0072] The heat treatment time is preferably 0.5-2 hours, for example 1 hour.
[0073] In the present invention, the silicon-carbon material and the solution containing the coupling agent are mixed by, for example, stirring.
[0074] The stirring time is preferably 0-2 h and not 0, for example 30 min or 1 h.
[0075] The stirring rate is preferably 500-2000 r / min, for example 1000 r / min.
[0076] In certain specific embodiments of the present invention, the silicon-carbon intermediate material and the conductive carbon material are mixed, for example, by stirring.
[0077] The stirring time is preferably 0-2 h and not 0, for example 30 min or 1 h.
[0078] The stirring rate is preferably 500-2000 r / min, for example 1000 r / min.
[0079] In the present invention, the silicon-carbon material, coupling agent and conductive carbon material are used to form the silicon-carbon core, coupling agent layer and conductive carbon layer of the silicon-carbon composite material respectively by the above method, and the mass loss of each material during the preparation process can be ignored.
[0080] The present invention also provides a silicon-carbon composite material obtained by the preparation method of the silicon-carbon composite material.
[0081] The present invention also provides a pole piece, which comprises the above silicon-carbon composite material.
[0082] The present invention also provides a battery, which comprises the above-mentioned pole piece.
[0083] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0084] The reagents and raw materials used in the present invention are commercially available.
[0085] The positive and progressive effects of the present invention are:
[0086] The silicon-carbon composite material of the present invention adopts molecular grafting technology and utilizes hydrogen bonding and electrostatic adsorption to make the conductive carbon material firmly coated on the surface of the silicon-carbon material, thereby reducing the possibility of the conductive carbon material falling off during use. At the same time, during high compaction or cyclic expansion, the stress generated can be released by breaking the hydrogen bonds, thereby improving the material's compressive resistance and reducing the agglomeration of the conductive carbon material.
[0087] The silicon-carbon composite material prepared by the present invention has a low expansion rate when prepared into an electrode, and has excellent cycle stability when prepared into a battery, and also has excellent first charge capacity and first efficiency. In the production process, the use of the silicon-carbon composite material of the present invention can reduce the production cost of the entire battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 This is the composite process of the silicon-carbon material of Example 1 and ATPMS.
[0089] Figure 2 This is the composite process of the silicon-carbon intermediate material and CNT in Example 1.
[0090] Figure 3 This is the SEM-TEM image of Comparative Example 1.
[0091] Figure 4 This is the SEM-TEM image of Example 1. DETAILED DESCRIPTION
[0092] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0093] The raw material information used in the following examples and comparative examples is shown in Table 1:
[0094] factory model APTMS Aladdin Ltd. / CNT Aladdin Ltd. /
[0095] Among them, the specific preparation process of silicon carbon material is as follows:
[0096] The porous carbon was placed in a fluidized bed apparatus, and then the temperature was raised to 500°C in a nitrogen atmosphere (flow rate of 40 L / min), and monosilane was introduced at a flow rate of 10 L / min. After heating to 550°C, the temperature was kept constant for 6.5 hours. After the reaction was completed, acetylene gas was introduced for CVD carbon coating at a flow rate of 10 L / min to obtain a silicon-carbon material, recorded as Si-C. The mass content of hydroxyl groups in Si-C was 1%, the mass content of silicon in Si-C was 50%, the mass content of porous carbon in Si-C was 47%, and the mass content of the carbon coating layer formed after CVD carbon coating in Si-C was 3%.
[0097] The mass content of hydroxyl groups in silicon-carbon materials is determined by the following method:
[0098] Weigh 2g of silicon-carbon material, record it as W, and put it into a 100mL conical flask, add 80mL of 0.05N sodium hydroxide aqueous solution, cover the conical flask, and stir the mixture at room temperature for 24 hours with a magnetic stirrer. Then separate the mixture by centrifugation, and take 10mL of the solution obtained by centrifugation. Before the titration process, add 0.5g of phenolphthalein to a mixture of 50mL of ethanol and 50mL of distilled water. Use three drops of phenolphthalein solution as an indicator and further titrate with a certain volume of 0.05N hydrochloric acid aqueous solution (recorded as A) to neutralize (the color changes from purple to transparent). Repeat the above steps with a blank solution (0.05N sodium hydroxide, without silicon-carbon sample), and record the volume of hydrochloric acid used to neutralize the blank solution as B. Among them, the units of A and B are both mL. X is the amount of hydroxyl group per unit mass of silicon-carbon material, which is calculated as follows: X (mM / g) = (BA) * 0.05 * 8 / W; the mass content of hydroxyl group in silicon-carbon material = X * 17 * 100%.
[0099] The mass content of hydroxyl determined by the above titration method can be assisted by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) to determine whether the above determination results are accurate. The silicon-carbon material is lightly ground and then pressed into a sample with potassium bromide using a baking lamp in a drying room and pressed onto the ATR element using a pressure tower. The characteristic peak of hydroxyl in the analyzed substance (blank group, silicon-carbon material heat treated at 600°C for 30 minutes to remove surface hydroxyl) is used as the internal standard. The group of this characteristic peak remains unchanged in the infrared position of the reactant or product (silicon-carbon material), and then calculated based on the change in the peak area of the target group relative to the peak area of the internal standard group.
[0100] Example 1
[0101] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0102] S1: Preparation of silicon-carbon intermediate material (Si-C@APTMS material)
[0103] Prepare an APTMS ethanol solution with a mass concentration of 1%, then mix and stir 500g of Si-C and about 1L of APTMS ethanol solution for 30min, the mass percentage of APTMS to Si-C is 2%, the stirring rate is 500r / min, and then perform rotary evaporation to evaporate the ethanol to obtain Si-C@APTMS material; wherein the chemical formula of APTMS is C6H 17 The amino content of NO3Si and APTMS is 9%. The composite process of silicon-carbon material and ATPMS is as follows: Figure 1 shown.
[0104] S2: Preparation of silicon-carbon composite materials
[0105] Based on 500g of Si-C, the Si-C@APTMS material obtained by S2 was added to ethanol for dissolution, and then 2.5g of CNT (the mass percentage of conductive carbon material in Si-C was 0.5%) was added and stirred for 30min at a stirring rate of 500r / min. Then, the ethanol was evaporated by rotary evaporation to obtain a silicon-carbon composite material; wherein, the field emission threshold electric field strength of CNT was 2V / μm, and the field emission current density was 1A / cm 2 The composite process of silicon-carbon intermediate material and CNT is as follows Figure 2 shown.
[0106] The silicon-carbon composite material comprises a silicon-carbon core, a coupling agent layer and a conductive carbon layer, wherein the coupling agent layer is connected to the silicon-carbon core through hydrogen bonds and is coated on the outer surface of the silicon-carbon core, and the conductive carbon layer is connected to the coupling agent layer through electrostatic action and is coated on the outer surface of the coupling agent layer.
[0107] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 97.5%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 2%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.5%.
[0108] Example 2
[0109] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0110] In S1, an APTMS ethanol solution with a mass concentration of 0.5% is prepared, and the mass percentage of APTMS to Si-C is 1%. The remaining steps are the same as in Example 1.
[0111] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 98.5%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 1%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.5%.
[0112] Example 3
[0113] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0114] In S1, an APTMS ethanol solution with a mass concentration of 3% is prepared, and the mass percentage of APTMS to Si-C is 6%. The remaining steps are the same as in Example 1.
[0115] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 93.9%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 5.6%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.5%.
[0116] Example 4
[0117] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0118] In S1, 500 g of Si-C and APTMS ethanol solution were mixed and stirred for 1 hour, and the remaining steps were the same as in Example 1.
[0119] Example 5
[0120] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0121] In S1, 500 g of Si-C and APTMS ethanol solution are mixed and stirred for 2 h, and the remaining steps are the same as in Example 1.
[0122] Example 6
[0123] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0124] The stirring rate in S1 is 1000 r / min, and the remaining steps are the same as in Example 1.
[0125] Example 7
[0126] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0127] The stirring rate in S1 is 2000 r / min, and the remaining steps are the same as in Example 1.
[0128] Example 8
[0129] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0130] In S2, the mass percentage of the conductive carbon material in Si-C is 0.01%, and the remaining steps are the same as in Example 1.
[0131] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 98.03%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 1.96%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.01%.
[0132] Example 9
[0133] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0134] In S2, the mass percentage of the conductive carbon material in Si-C is 2%, and the remaining steps are the same as in Example 1.
[0135] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 96%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 2%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 2%.
[0136] Example 10
[0137] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0138] CNT was added into S2 and stirred for 1 h. The remaining steps were the same as those in Example 1.
[0139] Embodiment 11
[0140] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0141] CNT was added into S2 and stirred for 2 h. The remaining steps were the same as those in Example 1.
[0142] Example 12
[0143] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0144] The stirring rate in S2 is 1000 r / min, and the remaining steps are the same as in Example 1.
[0145] Example 13
[0146] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0147] The stirring rate in S2 is 2000 r / min, and the remaining steps are the same as in Example 1.
[0148] Embodiment 14
[0149] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0150] In S2, ethanol is evaporated by rotary evaporation and then heat treatment is performed. The heat treatment temperature is 400° C. and the heat treatment time is 1 hour. The remaining steps are the same as in Example 1.
[0151] Embodiment 15
[0152] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0153] In S2, ethanol is evaporated by rotary evaporation and then heat treatment is performed. The heat treatment temperature is 400° C. and the heat treatment time is 0.5 h. The remaining steps are the same as in Example 1.
[0154] Example 16
[0155] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0156] In S2, ethanol is evaporated by rotary evaporation and then heat treatment is performed. The heat treatment temperature is 400° C. and the heat treatment time is 2 h. The remaining steps are the same as in Example 1.
[0157] Embodiment 17
[0158] The silicon-carbon composite material of this embodiment is prepared by the following steps:
[0159] S1: Preparation of silicon-carbon intermediate material (Si-C@APTMS material)
[0160] A 1% APTMS ethanol solution was prepared, and then 500 g of Si-C and about 1 L of APTMS ethanol solution were mixed and stirred for 30 min, so that the mass percentage of APTMS in Si-C was 2%, and the stirring rate was 500 r / min. Then, the ethanol was evaporated by rotary evaporation to obtain Si-C@APTMS material; wherein the chemical formula of APTMS is C6H17 NO3Si, the amino content of APTMS is 9%.
[0161] S2: Preparation of silicon-carbon composite materials
[0162] Based on 500g of Si-C, the Si-C@APTMS material obtained by S2 was added to ethanol for dissolution, and then 2.5g of CNT was added and stirred for 30min at a stirring rate of 500r / min, so that the mass percentage of the conductive carbon material in the Si-C@APTMS material was 0.5%, and then it was passed into an open spray drying equipment at a feed rate of 20L / min for spray drying to obtain a silicon-carbon composite material. The inlet air temperature of the spray drying was 150℃, and the outlet air temperature of the spray drying was 80℃; wherein, the field emission threshold electric field strength of CNT was 2V / μm, and the field emission current density was 1A / cm 2 .
[0163] The silicon-carbon composite material comprises a silicon-carbon core, a coupling agent layer and a conductive carbon layer, wherein the coupling agent layer is connected to the silicon-carbon core through hydrogen bonds and is coated on the outer surface of the silicon-carbon core, and the conductive carbon layer is connected to the coupling agent layer through electrostatic action and is coated on the outer surface of the coupling agent layer.
[0164] The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 97.5%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 2%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.5%.
[0165] Comparative Example 1
[0166] The silicon-carbon composite material of this comparative example is prepared by the following steps:
[0167] Si-C was added into ethanol to dissolve, and then CNT was added and stirred for 30 minutes at a stirring rate of 500 r / min, so that the mass percentage of Si-C in CNT was 0.5%, and then the ethanol was evaporated by rotary evaporation to obtain a silicon-carbon composite material.
[0168] Effect Example 1
[0169] 1. Electrochemical performance test:
[0170] Prepare the battery:
[0171] The silicon-carbon composite material prepared in the embodiment was mixed with the binder LA132 and the conductive agent Super P in a mass ratio of 70:20:10 to prepare a slurry, and the slurry was homogenized and coated on a copper foil, and vacuum dried and rolled to obtain a negative electrode sheet. A 1 mol / L LiPF6 electrolyte (the solvent is ethyl carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:1), a polypropylene microporous membrane as a diaphragm, and a metal lithium sheet as a counter electrode were used to assemble a button cell in an inert gas glove box system filled with argon to obtain a lithium-ion battery.
[0172] (1) First charge and discharge capacity and first effect
[0173] The lithium ion battery prepared above was charged and discharged at a voltage of 0.01-1.5V and a current density of 0.1A / g to obtain the first charge capacity and the first discharge capacity. The first efficiency was obtained by calculating the first charge capacity / first discharge capacity*100%.
[0174] (2) 400-cycle capacity retention rate
[0175] The lithium-ion battery prepared above was charged and discharged three times at a voltage of 0.01-1.5V and a current density of 0.1A / g, and then a charge and discharge cycle test was performed at a current density of 1A / g. The capacity retention rate was obtained after 400 cycles.
[0176] (3) Expansion rate
[0177] The initial thickness of the negative electrode sheet prepared above was tested, and the lithium-ion battery prepared above was subjected to a discharge-charge-discharge test at a voltage of 0.01-1.5 V and a current density of 0.1 A / g for 1.5 weeks. The battery was then disassembled and the final thickness of the negative electrode sheet was tested. The expansion rate was calculated by the following formula: expansion rate = (final thickness - initial thickness) / initial thickness * 100%.
[0178] The above test results are listed in Table 2:
[0179] Table 2
[0180] First charge capacity (mA·h / g) First effect (%) 400 cycles capacity retention rate (%) Expansion rate (%) Example 1 1813.1 91.30 90.87 100% Example 2 1820.2 91.00 85.32 120% Example 3 1733.2 90.10 92.3 88% Example 4 1810.2 91.41 91.25 92% Example 5 1812.4 91.50 91.58 92% Example 6 1811.7 91.42 91.34 90% Example 7 1814.2 91.53 91.73 90% Example 8 1800.1 90.21 86.87 115% Example 9 1741.2 91.40 93.1 85% Example 10 1820.2 91.45 91.25 91% Embodiment 11 1818.4 91.48 91.58 92% Example 12 1811.7 91.39 91.43 91% Example 13 1814.2 91.43 91.61 92% Embodiment 14 1843.1 91.20 90.80 100% Embodiment 15 1823.1 91.21 90.80 100% Example 16 1803.1 91.30 91.30 97% Embodiment 17 1844.5 90.70 81.14 120% Comparative Example 1 1834.5 90.50 80.64 135%
[0181] According to the data in Table 2, when the silicon-carbon composite material prepared in the embodiment of the present invention is prepared into an electrode, the expansion rate of the electrode can be achieved below 120%, and when it is prepared into a battery, the capacity retention rate of 400 cycles can be achieved to reach more than 81%, indicating that it has excellent cycle performance. At the same time, when it is prepared into a battery, it also has excellent first charge capacity and first efficiency.
[0182] Compared with Comparative Example 1 and Examples 1-3, as the APTMS content increases, the coating effect is higher, resulting in better cycle performance and lower expansion rate.
[0183] From the results of Examples 1 and 4-7, it can be seen that the mixing and stirring time of Si-C and APTMS ethanol solution in S1 is 1-2h, or the stirring rate is 1000-2000r / min, which can further improve the 400-cycle capacity retention rate and reduce the expansion rate. This may be because as the stirring time or stirring rate increases, APTMS is more evenly coated on Si-C, which is beneficial to its 400-cycle capacity retention rate and expansion rate.
[0184] From the results of Examples 1, 8 and 9, it can be seen that the mass percentage of Si-C@APTMS material in S2 to the conductive carbon material is 0.5%-2%, which can achieve a capacity retention rate of more than 90% and an expansion rate of less than 100% after 400 cycles. At the same time, it can also achieve an initial efficiency of more than 91% when it is prepared into a battery.
[0185] From the results of Examples 1 and 10-13, it can be seen that adding CNTs to S2 and stirring for 1-2 h, or a stirring rate of 1000-2000 r / min, can further improve the 400-cycle capacity retention rate and reduce the expansion rate. This may be because as the stirring time or stirring rate increases, the CNTs are more evenly coated on the Si-C@APTMS material, which is beneficial to its 400-cycle capacity retention rate and expansion rate.
[0186] It can be seen from the results of Example 1 and Example 17 that the preparation method of Example 1 of the present invention can further improve the first effect and 400 cycle capacity retention rate, and further reduce the expansion rate.
[0187] Effect Example 2
[0188] 1. SEM-TEM test: This test uses Elstar TM Electron column with resolution of 0.6 nm @ 30 kVSTEM, 0.6 nm @ 15 kV and 0.9* nm @ 1 kV, voltage range of 20* eV - 30 keV, and electron beam current range of 0.8 pA - 176 nA.
[0189] The silicon-carbon composite materials prepared in Example 1 and Comparative Example 1 were subjected to the above test. The test results of Comparative Example 1 are as follows: Figure 3 As shown, the test results of Example 1 are as follows Figure 4 As shown. Figure 3 It can be seen that the silicon-carbon composite material of Comparative Example 1 has the phenomenon of CNT agglomeration, while according to Figure 4It can be seen that the CNTs of Example 1 are relatively uniformly coated on the surface of the Si-C@APTMS material.
Claims
1. A silicon-carbon composite material, characterized in that: It includes a silicon-carbon core, a coupling agent layer and a conductive carbon layer from the inside to the outside. The coupling agent layer is connected to the surface of the silicon-carbon core through hydrogen bonds, and the conductive carbon layer is connected to the surface of the coupling agent layer through electrostatic action.
2. The silicon-carbon composite material according to claim 1, characterized in that: The mass percentage of the silicon-carbon core to the silicon-carbon composite material is 93%-99.5%, for example, 96%, 97.5%, 98.03% or 98.5%; And / or, the coupling agent layer accounts for 0.5%-6% by mass of the silicon-carbon composite material, for example, 1%, 1.96%, 2% or 5.6% by mass; And / or, the mass percentage of the conductive carbon layer to the silicon-carbon composite material is 0.01%-2%, for example, 0.5%; And / or, the silicon carbon core comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon; and / or, the surface of the silicon-carbon core contains hydroxyl groups; And / or, the coupling agent layer comprises a coupling agent, and the coupling agent is preferably a silane coupling agent, and more preferably a silane coupling agent containing amino groups and methyl groups, such as 3-aminopropyltrimethoxysilane; And / or, the conductive carbon layer comprises a conductive carbon material, and the conductive carbon material is preferably a carbon nanotube or graphene, more preferably a carbon nanotube; Wherein, the carbon nanotubes are preferably single-walled carbon nanotubes; And / or, the coupling agent layer is positively charged, and the conductive carbon layer is negatively charged.
3. The silicon-carbon composite material according to claim 1, characterized in that: The mass percentage of the silicon-carbon core in the silicon-carbon composite material is 97.5%, the mass percentage of the coupling agent layer in the silicon-carbon composite material is 2%, and the mass percentage of the conductive carbon layer in the silicon-carbon composite material is 0.5%; Alternatively, the silicon-carbon core accounts for 98.5% by mass of the silicon-carbon composite material, the coupling agent layer accounts for 1% by mass of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.5% by mass of the silicon-carbon composite material; Alternatively, the silicon-carbon core accounts for 93.9% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 5.6% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 0.5% of the mass percentage of the silicon-carbon composite material; Alternatively, the mass percentage of the silicon-carbon core to the silicon-carbon composite material is 98.03%, the mass percentage of the coupling agent layer to the silicon-carbon composite material is 1.96%, and the mass percentage of the conductive carbon layer to the silicon-carbon composite material is 0.01%; Alternatively, the silicon-carbon core accounts for 96% of the mass percentage of the silicon-carbon composite material, the coupling agent layer accounts for 2% of the mass percentage of the silicon-carbon composite material, and the conductive carbon layer accounts for 2% of the mass percentage of the silicon-carbon composite material.
4. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: S1, mixing a silicon-carbon material and a solution containing a coupling agent to obtain a silicon-carbon intermediate material; S2, mixing the silicon-carbon intermediate material and the conductive carbon material, and performing a second solvent removal to obtain a silicon-carbon composite material; Wherein, the silicon-carbon material and the coupling agent contain functional groups that can generate hydrogen bonds between the two; Wherein, the surface of the coupling agent and the surface of the conductive carbon material have opposite charges.
5. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The surface of the silicon-carbon material contains hydroxyl groups; wherein the mass content of the hydroxyl groups in the silicon-carbon material is preferably 0.5%-2%, for example, 1%; and / or, the surface of the coupling agent is positively charged; Preferably, the coupling agent contains an amino group, and the coupling agent also contains at least one of a methyl group and a hydroxyl group; Wherein, the mass content of the amino group of the coupling agent is 8%-10%, for example, 9%; and / or, the surface of the conductive carbon material is negatively charged; And / or, the field emission threshold electric field strength of the conductive carbon material is 1-3 V / μm, for example, 2 V / μm; And / or, the field emission current density of the conductive carbon material is 0.5-3A / cm 2 , for example 1A / cm 2 ; And / or, the coupling agent is a silane coupling agent, preferably a silane coupling agent containing amino and methyl groups, such as 3-aminopropyltrimethoxysilane; And / or, the solvent in the solution containing the coupling agent is, for example, one or more of methanol, ethanol, ethyl acetate, toluene and tetrahydrofuran; wherein the mass concentration of the coupling agent in the solution containing the coupling agent is preferably 0.5%-10%, for example, 1% or 3%; And / or, the conductive carbon material is a carbon nanotube or graphene, preferably a carbon nanotube; wherein the carbon nanotube is preferably a single-walled carbon nanotube; And / or, the silicon-carbon material comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon, and the silicon-carbon material has a silicon content of 40%-60% by mass, for example, 50%; And / or, the silicon-carbon material comprises porous carbon, silicon deposited in the porous carbon and a carbon layer coated on the surface of the porous carbon, and the mass content of the porous carbon is 37%-57%; And / or, the mass percentage of the coupling agent to the silicon-carbon material is preferably 0.5%-6%, for example 1%; And / or, the mass percentage of the conductive carbon material to the silicon-carbon material is 0.01%-2%, for example, 0.5%.
6. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The preparation of the silicon-carbon material comprises the following steps: mixing porous carbon and a gas silicon source for CVD silicon deposition, and then mixing with a gas carbon source for CVD carbon coating to obtain the silicon-carbon material; Wherein, the gaseous silicon source is preferably silane, and the silane is preferably monosilane; Wherein, the gaseous carbon source is preferably alkyne; the alkyne is preferably acetylene; The CVD silicon deposition preferably includes a heating stage and a heat preservation stage; the temperature of the heat preservation stage is preferably 100-600° C., for example, 550° C.; the time of the heat preservation stage is preferably 6-7 hours, for example, 6.5 hours; Wherein, the CVD silicon deposition is preferably carried out in nitrogen; wherein, the CVD silicon deposition is carried out, for example, in a fluidized bed; wherein, preferably, a gaseous silicon source is introduced into the fluidized bed when the porous carbon is heated to 500°C; wherein, the flow rate of the gaseous silicon source into the fluidized bed is preferably 5-20L / min, for example, 10L / min; wherein, the flow rate of the gaseous carbon source into the fluidized bed is preferably 5-20L / min, for example, 10L / min; wherein, the flow rate of the nitrogen is preferably 40L / min.
7. The method for preparing the silicon-carbon composite material according to claim 4, characterized in that: The second desolventizing method comprises spray drying and / or rotary evaporation; Wherein, the spray drying equipment is preferably an open spray drying equipment; Wherein, the inlet air temperature of the spray drying is preferably 100-180°C; Wherein, the outlet air temperature of the spray drying is preferably 50-90°C; Wherein, the feed rate of the spray drying is preferably 10-40 L / min; And / or, after mixing the silicon-carbon material and the solution containing the coupling agent, a first desolventizing step is further included; wherein the first desolventizing method is, for example, rotary evaporation; And / or, in step S2, the silicon-carbon intermediate material is dissolved and then mixed with the conductive carbon material; The solvent used for dissolving is, for example, one or more of methanol, ethanol, ethyl acetate, toluene and tetrahydrofuran; And / or, after the second solvent removal, a heat treatment step is also included; Wherein, the temperature of the heat treatment is preferably 400-800°C, for example 600°C; Wherein, the heat treatment time is preferably 0.5-2h, for example 1h; And / or, the silicon-carbon material and the solution containing the coupling agent are mixed by stirring; wherein the stirring time is preferably 0-2h and not 0, for example, 30min or 1h; wherein the stirring rate is preferably 500-2000r / min, for example, 1000r / min; And / or, the silicon-carbon intermediate material and the conductive carbon material are mixed by stirring; wherein, the stirring time is preferably 0-2h and not 0, for example, 30min or 1h; wherein, the stirring rate is preferably 500-2000r / min, for example, 1000r / min.
8. A silicon-carbon composite material obtained by the method for preparing a silicon-carbon composite material as claimed in any one of claims 4 to 7.
9. A pole piece, characterized in that: It comprises the silicon-carbon composite material as described in any one of claims 1-3 and 8.
10. A battery, characterized in that: It comprises the pole piece as claimed in claim 9.